2020
DOI: 10.3892/ol.2020.11327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of apigenin on whole transcriptome profile of TNFα‑activated MDA‑MB‑468 triple negative breast cancer cells

Abstract: The lack of hormone receptors in triple negative breast cancer (TNBC) is associated with the inefficacy of anti-estrogen chemotherapies, leaving fewer options for patient treatment and higher mortality rates. Additionally, as with numerous types of inflammatory breast cancer, infiltration of tumor associated macrophages and other leukocyte sub-populations within the tumor inevitably lead to aggressive, chemo-resistant, metastatic and invasive types of cancer which escape immune surveillance. These processes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…Recent studies have reported that CFB is associated with the prognosis of different types of cancer (32)(33)(34). A previous study has demonstrated that CFB is not only identified in all crypts in the colonic mucosa, but is also expressed in adenomas and carcinomas (16).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that CFB is associated with the prognosis of different types of cancer (32)(33)(34). A previous study has demonstrated that CFB is not only identified in all crypts in the colonic mucosa, but is also expressed in adenomas and carcinomas (16).…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 ] Apigenin could effectively reverse the cancer‐promoting effects of tumor necrosis factor‐α (TNF‐α) in breast cancer cell MDA‐MB‐231. [ 38,39 ] Apigenin also could promote the apoptosis of cisplatin‐resistant ovarian cancer cells (SKOV3 and DDPs) by targeting Mcl‐1 in a mitochondrial‐dependent way. [ 40 ] Growing evidences indicate that apigenin exerts anti‐cancer effect via different mechanisms in the various cancer models.…”
Section: The Anti‐cancer Effects Of Dietary Polyphenolsmentioning
confidence: 99%
“…In the study of apigenin regulating the pro-inflammatory activation of TNFα in MD-MB-468 cells of Triple-Negative Breast Cancer (TNBC). Several TNFα deferentially upregulated transcripts were reduced by apigenin, including CXCL10 , C3 , PGLYRP4 , IL22RA2 , KMO , IL7R , ROS1 , CFB , IKBKe , SLITRK6 (a checkpoint target), and MMP13 [ 46 ]. The SLITRK1 , SLITRK2 , SLITRK3 , SLITRK4 , SLITRK5 , and SLITRK6 genes have been detected in the human brain, and the expression profile of each SLITRK is unique.…”
Section: Discussionmentioning
confidence: 99%